P62 How much of the disability-related inequalities in health and well-being are mediated by barriers to participation faced by people with disabilities? A causal mediation analysis using longitudinal data from working age people with and without disabilities in great britain. (3rd September 2019) - Aitken, Z; Disney, G; Krnjacki, L; Milner, A; Emerson, E; Kavanagh, AM
Abstract : Background: Large health inequalities exist between people with and without disabilities, including many health conditions unrelated to the impairment causing the disability. There is some evidence that these health inequalities are, in part, due to the poor socio-economic circumstances experienced by people with disabilities, and therefore are amenable to public health intervention. In this study, we used a unique dataset to examine the relationship between disability acquisition and subsequent health outcomes using five different measures of health and wellbeing. We quantified the extent to which social barriers to participation explained the health inequalities between people with and without disability. Methods: We used data from three waves of the Life Opportunities Survey, a longitudinal study of disability in Great Britain with a strong focus on barriers to participation in society. We compared health and well-being outcomes between adults who recently acquired an impairment and those who remained disability-free, adjusting for baseline demographic, socio-economic and health characteristics. Health and well-being outcomes included: self-rated health measured on a five-point scale, and life satisfaction, feeling that life is worthwhile, happiness, and anxiety, measured on eleven-point Likert scales. We conducted a causal mediation analysis to quantify natural indirect effects representing how much of the effect of disability acquisition on each outcome was explained by barriers to participation including employment, economic life, transport, leisure activities, social contact and accessibility. We used multiple imputation with 50 imputed datasets to account for missing data and conducted analyses in Stata/SE 15. Results: There was evidence that people who had recently acquired a disability had poorer health and well-being compared to people with no disability. Barriers to participation explained 13% (95% CI 11%, 14%) of inequalities in self-rated health, and were higher for all measures of well-being: life satisfaction (43%, 95% CI 39%, 47%), feeling that life is worthwhile (36%, 95% CI 31%, 40%), happiness (46%, 95% CI 39%, 53%) and anxiety (27%, 95% CI 24%, 31%). Conclusion: Despite methodological limitations including strong assumptions about confounding and potential selection bias from missing data, this is the first study to quantify how much of the inequalities in health and well-being between people with and without disabilities are explained by social barriers to participation. We found that a substantial proportion of the inequalities in health and well-being experienced by people with recently acquired disabilities were driven by social barriers to participation. The findings that some of these differences are socially produced have important policy implications, highlighting modifiable factors amenable to public health interventions to target the mechanisms causing the health inequalities.